Gender perspective on the existence of women with single parent status (case study of the women head of household community in Mojosongo, Central Java) - kurnia, Kurnia Atika Suri; Haryani Saptaningtyas; Akbarudin Arif (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Women as single parents are one of the social phenomena that often cause negative stigma from society. This study aims analyzes the gender perspective on single-parent women and their destigmatization strategies in society, with a case study on the women head of household community in Mojosongo Village, Central Java. The method used in this study is descriptive qualitative, with a gender perspective approach. The data of this study was obtained from observation, interviews, and documentation. The selection of key and primary informants used purposive sampling, while the selection of supporting informants used snowball sampling. The data analysis technique in this study is an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing stages. The results of the study indicate that there are differences in stigma for women and men when they become single parents, especially single parents, due to divorce cases (divorcee). They get a worse negative stigma than single parents because of the death of their husbands case (widow). Therefore, destigmatization strategies must be carried out by both divorcees and widows. One of these strategies is joining the women head of household community, which empowers single-parent women. The existence of the women head of household community can be an effort to reduce or even eliminate negative stigma in society because it can empower single parents socially and economically through various activity programs that improve their lives in society. Keywords: Gender Perspective, Single Parents, Women Head of Household, Destigmatization, Community Empowerment